Effects of Charge Transfer on the Adsorption of CO on Small Molybdenum‐Doped Platinum Clusters. Issue 17 (22nd February 2017) - Ferrari, Piero; Vanbuel, Jan; Tam, Nguyen Minh; Nguyen, Minh Tho; Gewinner, Sandy; Schöllkopf, Wieland; Fielicke, André; Janssens, Ewald
Abstract: The interaction of carbon monoxide with platinum alloy nanoparticles is an important problem in the context of fuel cell catalysis. In this work, molybdenum‐doped platinum clusters have been studied in the gas phase to obtain a better understanding of the fundamental nature of the Pt–CO interaction in the presence of a dopant atom. For this purpose, Pt n + and MoPt n −1 + ( n= 3–7) clusters were studied by combined mass spectrometry and density functional theory calculations, making it possible to investigate the effects of molybdenum doping on the reactivity of platinum clusters with CO. In addition, IR photodissociation spectroscopy was used to measure the stretching frequency of CO molecules adsorbed on Pt n + and MoPt n −1 + ( n= 3–14), allowing an investigation of dopant‐induced charge redistribution within the clusters. This electronic charge transfer is correlated with the observed changes in reactivity. Abstract : Doping effects : The effects of single‐atom molybdenum doping on the bonding of CO to small cationic platinum clusters have been studied by a combination of mass spectrometry, IR photodissociation spectroscopy (see figure), and DFT calculations. The interaction of the clusters with CO was found to be affected by doping in a size‐dependent manner, which has been traced to molybdenum‐induced alterations of the electronic density of the clusters.